PSIKOLOGI PERKEMBANGAN PERIODE PRANATAL - Lestari, Ni Gusti Ayu Made Yeni; Ekaningtyas, Ni Luh Drajati (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study aims to determine the importance of the prenatal or pregnancy period for the growth and development of individuals in the future, based on a developmental psychology approach. Based on the results of the study, it was concluded that the prenatal period is an important period because in this period basic things are formed, such as genetic innate traits, gender, position of the order of children, and number of children. In addition there are things that must be considered during the prenatal period such as nutrition and maternal health, vitamins, rhesus, drugs, alcohol, cigarettes or tobacco, x-rays, as well as maternal emotions during pregnancy. The psychology of the development of the prenatal period provides an overview of special characteristics, important conditions, and things that need to be considered during the prenatal period so that relevant parties can support the creation of a posivite environment for pregnant women and the fetus in the womb